Analysis of the Effectiveness of Content Marketing Communications in the Effort of Formulating a Promotion Strategy to Stimulate Repetitive Purchases - Medina Ramadhany; Arianis Chan; Cecep Safa’atul Barkah; Tetty Herawaty (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to see how the level of effectiveness of content marketing communication to consumers at the Bajumantanmoo online store in driving repeat purchase decisions. This research uses quantitative methods with a descriptive approach. Samples were taken using purposive sampling technique and data were collected through questionnaires to the sample. The data then tested using the validity test with the t table value (0.3297) and the reliability test with a Cornbach alpha value of 1.08. Based on the research results, it was found that the persuasion indicator was the content marketing indicator with the least value in encouraging consumers to make repeat purchases.